The anti-hyperlipidemic effect of a formulated diet containing Tetrapleura tetraptera fruits and Xanthosoma sagittifolium leaves in adult wistar rats - Odejide, Iyanuoluwa Timileyhin (Biochemistry,Obafemi Awolowo University, 2023)
xvi,108p